Psychological interventions in times of crisis - Barbanel, Laura; Sternberg, Robert J. (Springer Pub., 2006)
There is controversy as to whether psychological interventions in the aftermath of disaster are helpful or not. This book addresses these controversies and describes the responses that psychologists have made in different parts of the world to disaster.